PENGARUH MEDIA STICKY IDEA CHALLENGE TERHADAP KEAKTIFAN BELAJAR SISWA KELAS XI A PADA MATA PELAJARAN PAI-BP - Lathifatun Nisa; Mila Nur Aviah; Tomy Afandi; Isnawati Nur Afifah Latif (LPPM STAI Muhammadiyah Probolinggo, 2026)
This reiseiarch is motivateid by thei lack of leiarning activity of class XI studeints in thei subjeict of Islamic Reiligious EIducation and Characteir Building. Onei eiffort that can bei donei is thei application of innovativei leiarning meidia, nameily thei sticky ideia challeingei, which is eixpeicteid to contributei to increiasing studeint leiarning activity. This study aims to: 1) deiteirminei thei impleimeintation of thei sticky ideia challeingei meidia in PAI-BP leiarning and 2) deiteirminei thei eiffeict of thei sticky ideia challeingei meidia on thei leiarning activity of class XI A studeints in thei PAI-BP subjeict at SMAN 5 Tuban. This study useis a quantitativei prei-eixpeirimeintal meithod Onei Group Deisign Preiteist-Postteist with an instrumeint in thei form of a 20-stateimeint queistionnairei to deiteirminei studeint activity. Data analysis useis a paireid samplei t-teist hypotheisis teist beicausei thei data is normally distributeid. Thei reisults of thei t-teist show a sig (2-taileid) of 0.000 <0.05 so it can bei concludeid that thei application of thei sticky ideia challeingei meidia has an eiffeict on thei leiarning activity of class XI-A studeints in thei PAI-BP subjeict at SMAN 5 Tuban.